2023
DOI: 10.1037/pag0000741
|View full text |Cite
|
Sign up to set email alerts
|

Do disfluencies increase with age? Evidence from a sequential corpus study of disfluencies.

Abstract: Speech disfluencies such as repeated words and pauses provide information about the cognitive systems underlying speech production. Understanding whether older age leads to changes in speech fluency can therefore help characterize the robustness of these systems over the life span. Older adults have been assumed to be more disfluent, but current evidence is minimal and contradictory. Particularly noteworthy is the lack of longitudinal data that would help establish whether a given individual's disfluency rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(195 reference statements)
1
1
0
Order By: Relevance
“…In contrast to more silent pauses, older adults used fewer lexical fillers (e.g., "you know") than younger adults across all picture types, and there were no age differences in filled pauses (e.g., "um"). Finding age differences in the production of some disfluencies but not others is consistent with previous literature (Abrams & White, 2023;Kavé & Goral, 2017) and can result from the specific measures used to assess fluency (Beier et al, 2023) and greater variability in older adults' disfluencies (Saryazdi et al, 2019). The present results suggest that emotional content is another factor that further delineates when age-related differences in disfluencies do or do not occur.…”
Section: Disfluenciessupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to more silent pauses, older adults used fewer lexical fillers (e.g., "you know") than younger adults across all picture types, and there were no age differences in filled pauses (e.g., "um"). Finding age differences in the production of some disfluencies but not others is consistent with previous literature (Abrams & White, 2023;Kavé & Goral, 2017) and can result from the specific measures used to assess fluency (Beier et al, 2023) and greater variability in older adults' disfluencies (Saryazdi et al, 2019). The present results suggest that emotional content is another factor that further delineates when age-related differences in disfluencies do or do not occur.…”
Section: Disfluenciessupporting
confidence: 92%
“…Even without explicit emotion regulation, Burbridge et al (2005) found that younger and middle-aged adults made more reference errors (another type of disfluency) when describing experiences in which they felt a negative emotion, relative to positive and neutral experiences. One limitation of these studies is that only one type of disfluency was measured, an issue that becomes relevant when investigating age-related differences in disfluencies because older adults are not consistently more disfluent than younger adults (e.g., Beier et al, 2023; see Abrams & White, 2023, for a review).…”
Section: Emotion Regulation In Aging and Its Relationship To Speech P...mentioning
confidence: 99%